Evaluation methodology for assessing the effectiveness of sports techniques - Lanka, J.; Konrads, A.; Shalmanov, A. (ISBS - Conference Proceedings Archive (Konstanz), 2005)
The purpose of this study was to introduce with the methodology and long-term research results of sports technique effectiveness. In the research, using sport throwings as an example of a difficult movement, we worked out the evaluation methodology of the movement technique quality and ideas of this methodology can be used not only for the evaluation of shot-put, but also for other movement technique.